The history of time : a very short introduction - Holford-Strevens, Leofranc (Very short introductions, 2005)
Why do we measure time in the way that we do? Why is a week seven days long? At what point did minutes and seconds come into being? Why are some calendars lunar and some solar? The organisation of time into hours, days, months and years seems immutable and universal, but is actually far more artificial than most people realise. The French Revolution resulted in a restructuring of the French calendar, and the Soviet Union experimented with five and then six-day weeks. Leofranc Holford-Strevens explores these questions using a range of fascinating examples from Ancient Rome and Julius Caesar's imposition of the Leap Year, to the 1920s' project for a fixed Easter.